Interim return and palestine: Onpolitics, terminology and structural invisibility - Riina Isotalo (Danish Institute for International Studies (DIIS), 2006)
Taking its cue from the literature on return migration and repatriation processes as well as the Palestinian refugee problem, this paper looks first at the issue of return to place of origin or not. Return migration to the West Bank and Gaza Strip is then considered in the light of this schema, and stipulations of the politicisation of a transnational paradigm and the structural invisibility of return migration are highlighted. The present paper argues that in the Palestinian context, return is a political issue for all parties concerned and that Palestinian return migration has been structurally invisible. The paper concludes that politicisation of a transnational paradigm should be acknowledged in studying Palestinians' transnational mobility and relations because otherwise the fact that some transnational practises might aim at permanent return can pass unnoticed.
Keywords: 330; Internationale Wanderung; Rückwanderung; Flüchtlinge; Palästina